Analisis Profitabilitas Pada PT Unilever Indonesia, Tbk - Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2020)
The purpose of this research is to determine the performance of PT Unilever Indonesia as seen from the company’s ability to generate profits. The financial statements studied are financial reports that have been published on IDX. The periode of the financial statements studied is a period of 5 years, from 2014 to 2018. From the results of the study, it can be seen that the company’s ability to generate profits can be concluded very well. This is because trends resulting from profit margin ratios and return on assets show an upward trend in profits. The return on equity profit ratio does not invrease. However, the company still gets a high profit